Malignant Primary Extradural Meningioma in Elderly Patients: Report of Two Cases and Literature Review - Hsin-Yao Lin; Tung-Ying Chen; Cheng-Chia Tsai (International Journal of Gerontology, 2015)
Primary extradural meningioma, also known as ectopic meningioma, is uncommon and represents ∼2% of all meningiomas. Malignant primary extradural meningioma is even more rare. The rarity of cases means the condition is not readily suspected or diagnosed. In this report, we present one case of primary extradural meningioma in elderly patients who presented with a scalp nodule and another highly suspected case. Both patients underwent surgical resection of the tumors. Histological study and immunostaining confirmed the diagnosis. We also conducted a literature review regarding similar cases. Surgical resection with a wide margin remains the first choice of treatment.